2017
DOI: 10.4081/thal.2017.6354
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Types of Thalassemias and Hemoglobinopathies: Study in a Tertiary Level Children Hospital in Bangladesh

Abstract: Thalassemias and hemoglobinopathies are the most common hemolytic congenital disorders in Bangladesh as in many parts of the world. This study was done to find the common types of thalassemias and abnormal hemoglobin variants seen in Bangladeshi populations. A total of 4813 samples were analyzed for hemoglobin disorders out of which 2308 (49.95%) showed abnormalities. The samples were analyzed by Bio Rad D 10 Analyzer in 3914 (81.32%) cases, BIORAD VARIANTβ thalassemia short program using the principle of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…One reason for this paucity of data could be the low prevalence of sickle haemoglobin in some countries in South Asia. For instance, studies from Sri Lanka and Bangladesh have shown that the prevalence of sickle haemoglobin was relatively lower than that of other haemoglobinopathies in these regions [63][64][65]. Sickle haemoglobin has been reported at comparatively higher prevalence from the Tharu community of Western Nepal and Pakistan [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this paucity of data could be the low prevalence of sickle haemoglobin in some countries in South Asia. For instance, studies from Sri Lanka and Bangladesh have shown that the prevalence of sickle haemoglobin was relatively lower than that of other haemoglobinopathies in these regions [63][64][65]. Sickle haemoglobin has been reported at comparatively higher prevalence from the Tharu community of Western Nepal and Pakistan [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…1a, the first-generation dendrimer (G1-Cys) was synthesized stepwise from b-CD via the Williams and Sharpless reactions, referring to our previous study. 35 G1-Cys was characterized by the 1 H NMR spectrum, which could be ascribed to the terminal allyl groups, glycerol ether, and D-galactose of b-CD moieties in the dendrimers (Fig. 1b).…”
Section: Characterizationmentioning
confidence: 99%
“…The first-generation dendrimer (G1-Cys) was synthesized via the Williams and Sharpless reactions as in our previous research. 35 Briefly, NaH and dried N,N-dimethylformamide (DMF) were mixed. b-Cyclodextrin (b-CD) in DMF solution was then added dropwise.…”
Section: Synthesismentioning
confidence: 99%
“…Thalassemias and hemoglobinopathies are the most common inheritant hemolytic congenital disorders in Bangladesh. 1 Haemoglobinopathies denote genetic defects collectively affecting either haem structure or synthesis. 1 They are divided into two categories.…”
Section: Introductionmentioning
confidence: 99%